Kinetic Study of Heavy Metals Removal from Pharmaceutical Wastewater Using Geopolymer/Fe3O4 Nanocomposite - Tsado Mathew, John; Monday, Musah; Azeh , Yakubu; Mohammed, Musa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The pharmaceutical industry, while essential for public health, is a significant contributor to environmental pollution due to the generation of wastewater containing heavy metals. The nanocomposite was characterized using X-ray diffraction (XRD), High-resolution scanning electron microscopy (HRSEM)/energy dispersive spectroscopy (EDS) and Fourier transmission infrared spectroscopy (FTIR). The XRD analysis of the nanocomposite identified indexed as (220), (311), (400), (422), (511), (440), (620), and (533) with respective 2θ values of 32.8°, 35.7°, 44.5°, 53.4°, 57.7°, 64.1°, 71.8°, and 75.1°, can be attributed to the diffraction patterns of Fe3O4 crystals, as per the standard data (JCPDS number, 00–43-0317). Additionally, a sharp and intense peak at 2θ = 26.90° corresponds to the presence of amorphous SiO2 within the matrix sample. The HRSEM image of the nanocomposite exhibited spherical-shaped structures of geopolymer/Fe3O4, and some irregular shapes. The effects of the contact time, temperature and dosage on the removal percentage of heavy metal ions were studied. The kinetics and thermodynamics of heavy metal adsorption onto the nanocomposites were investigated, providing insights into the adsorption mechanisms and efficiency. The results indicated that the adsorption process followed pseudo-second-order kinetics, suggesting chemisorption as the dominant mechanism. Thermodynamic studies demonstrated that the adsorption of heavy metals onto the nanocomposites was spontaneous and exothermic, indicating the feasibility and efficiency of the process. The findings of this research contribute to the development of innovative and eco-friendly approaches to mitigate the impact of heavy metals in industrial wastewater, promoting both environmental sustainability and regulatory compliance in the pharmaceutical sector.